Analisis Kebutuhan Pelatihan: Model yang disarankan untuk Pelatihan Aparatur - Sifak; Tukiran, Martinus (AGUSPATI Research Institute, 2024)
Implementation The current implementation of apparatus training has not provided significant results in increasing apparatus competency. The gap between training materials and the competencies required by participants still exists. Post-evaluation results of technical training show that only 75% of the material received in class can be implemented in apparatus work. One of the problems that contributes to curriculum gaps is the inaccurate implementation of training needs analysis. TNA is very useful as a basis for the success of a training program. The main stages of TNA involve a number of logical steps of identifying problem needs, determining a needs analysis design, collecting data, analyzing data, and providing feedback. This paper hopes to contribute to knowledge about TNA by developing a conceptual framework, which provides guidance for the implementation of TNA in ASN training programs